Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

Effects of region, demography, and protection from fishing on batch fecundity of common coral trout (Plectropomus leopardus) - Alex B. Carter; Campbell R. Davies; Bruce D. Mapstone; Garry R. Russ; Andrew J. Tobin; Ashley J. Williams (Coral Reefs, 2014)

Spatial variation in the effects of size and age on reproductive dynamics of common coral trout Plectropomus leopardus - A. B. Carter; G. R. Russ; A. J. Tobin; A. J. Williams; C. R. Davies; B. D. Mapstone (Journal of Fish Biology, 2014)
The effects of size and age on reproductive dynamics of common coral trout Plectropomus leopardus populations were compared between coral reefs open or closed (no‐take marine reserves) to fishing and among four geographic regions of the Great Barrier Reef ( GBR ), Australia. The specific reproductive metrics investigated were the sex ratio, the proportion of vitellogenic females and the spawning fraction of local populations. Sex ratios became increasingly male biased with length and age, as expected for a protogyne, but were more male biased in southern regions of the GBR (Mackay and Storm Cay) than in northern regions (Lizard Island and Townsville) across all lengths and ages. The proportion of vitellogenic females also increased with length and age. Female P. leopardus were capable of daily spawning during the spawning season, but on average spawned every 4·3 days. Mature females spawned most frequently on Townsville reserve reefs (every 2·3 days) and Lizard Island fished reefs (every 3·2 days). Females on Mackay reefs open to fishing showed no evidence of spawning over 4 years of sampling, while females on reserve reefs spawned only once every 2–3 months. No effect of length on spawning frequency was detected. Spawning frequency increased with age on Lizard Island fished reefs, declined with age on Storm Cay fished reefs, and declined with age on reserve reefs in all regions. It is hypothesized that the variation in P. leopardus sex ratios and spawning frequency among GBR regions is primarily driven by water temperature, while no‐take management zones influence spawning frequency depending on the region in which the reserve is located. Male bias and lack of spawning activity on southern GBR , where densities of adult P. leopardus are highest, suggest that recruits may be supplied from central or northern GBR . Significant regional variation in reproductive traits suggests that a regional approach to management of P. leopardus is appropriate and highlights the need for considering spatial variation in reproduction where reserves are used as fishery or conservation management tools.

Comparative biology of tropical Lethrinus species (Lethrinidae): challenges for multi‐species management - L. M. Currey; A. J. Williams; B. D. Mapstone; C. R. Davies; G. Carlos; D. J. Welch; C. A. Simpfendorfer; A. C. Ballagh; A. L. Penny; E. M. Grandcourt; A. Mapleston; A. S. Wiebkin; et al. (Journal of Fish Biology, 2013)
Life‐history characteristics of six tropical Lethrinus species sampled from the Great Barrier Reef World Heritage Area were compared. Two species groups were identified based on fork length ( L F ): large species with maximum L F > 640 mm (longface emperor Lethrinus olivaceus , yellowlip emperor Lethrinus xanthochilus and spangled emperor Lethrinus nebulosus ) and small species with maximum L F 480 mm (Pacific yellowtail emperor Lethrinus atkinsoni , pink ear emperor Lethrinus lentjan and ornate emperor Lethrinus ornatus ). Lifespan was not correlated with L F . Early growth for all species was rapid and similar during the first few years of life, but coefficients of the von Bertalanffy growth function varied considerably among species. Growth also differed between sexes for L. atkinsoni . Reproductive characteristics varied among species, with peak periods of spawning occurring in November to December for L. atkinsoni , July to August for L. nebulous , September to October for L. olivaceus and a protracted season for L. lentjan , although fewer samples were available for the last two species. Sex‐specific L F and age distributions and gonad histology of L. lentjan were suggestive of a functional protogynous reproductive pattern, as observed in other lethrinids. Gonad histology indicated non‐functional protogynous hermaphroditism for L. atkinsoni and L. nebulosus . The diversity of life histories among these closely related species emphasizes the difficulty in devising single management strategies appropriate for multi‐species fisheries and illustrates the importance of understanding species‐specific life histories to infer responses to exploitation.

Spatial and interannual patterns in growth of an exploited coral‐reef fish - A. J. Williams; B. D. Mapstone; C. R. Davies (Journal of Fish Biology, 2007)
Patterns of growth in an exploited reef fish Lethrinus miniatus were examined over 5 years (1995–1999) at two spatial scales: (1) among regions of the Great Barrier Reef (GBR) separated by >100 km and (2) among reefs within each of these regions, separated by ≤10 km. Mean annual growth of L. miniatus varied significantly among years, but this variation was consistent among ages and regions, indicating that factors that influence temporal patterns in growth were not age‐specific and operated at relatively large spatial scales. Significant variation in growth was also observed among some reefs within regions, although the greatest variation was among regions. The average maximum fork length ( ) and average maximum mass ( M ∞ ) varied significantly among regions, suggesting that productivity of L. miniatus is likely to vary among regions of the GBR. There was also significantly greater mass of fish for a given L F in two regions, which magnified the regional differences in M ∞ . The observed temporal and spatial variation in growth highlighted the importance of a multi‐scale approach to population studies and assessment of fish stocks.

Reproductive biology of a large, aggregation‐spawning serranid, Epinephelus fuscoguttatus (Forsskål): management implications - R. J. Pears; J. H. Choat; B. D. Mapstone; G. A. Begg (Journal of Fish Biology, 2007)
The reproductive biology of Great Barrier Reef populations of the long‐lived grouper Epinephelus fuscoguttatus (brown‐marbled grouper or flowery cod) was investigated using histological analyses. Evidence provided by gonad morphology and age‐based demographics suggested monandric protogynous hermaphroditism. Younger age groups contained only immature and mature females, and all males were above the size and age of 100% female maturity, consistent with secondary males derived from mature females by adult sex change. Fishing records confirmed that spawning aggregations of this species and the co‐occurring Epinephelus polyphekadion (camouflage grouper) are sometimes targeted on the Great Barrier Reef. Sampling data revealed strong spawning seasonality for E. fuscoguttatus , with a relatively narrow annual spawning period (November to January). The temporal pattern of reproductive activity within the spawning period, based on occurrence of near spawning ovaries (containing hydrated oocytes), indicated spawning events may occur throughout much of the lunar cycle and only partly coincide with seasonal fishing closure periods on the Great Barrier Reef. The results indicate that protection would be enhanced by a longer seasonal closure.

Effects of size and fragmentation of marine reserves and fisher infringement on the catch and biomass of coral trout, Plectropomus leopardus , on the Great Barrier Reef, Australia - L. R. LITTLE; A. D. M. SMITH; A. D. MCDONALD; A. E. PUNT; B. D. MAPSTONE; F. PANTUS; C. R. DAVIES (Fisheries Management and Ecology, 2005)
A spatially structured simulation model of the population dynamics and line fishing exploitation of common coral trout, Plectropomus leopardus Lacepède, was used to evaluate the effects of infringement and different amounts and arrangements of marine reserves on the Reef Line Fishery of the Great Barrier Reef, Australia. With no marine reserves and under a constant future effort level equal to that for 1996, the size of the population was reduced and the biomass stabilised at about 40% of pre‐exploitation levels. Marine reserves were ineffective at conserving biomass when limited infringement was allowed throughout an entire reserve. When infringement was absent altogether or limited to the edges of reserves, larger marine reserves lead to lower total catches and higher overall biomass. When infringement was limited to reserve edges, a single large closure was more effective at conserving biomass than more fragmented arrangements. Simulations suggested that marine reserves might lead to better conservation of a fishery‐targeted species if infringement is negligible or limited to reserve margins. Even where infringement occurred only at the edges of reserves, a network of small reserves may be less effective at conserving a targeted species than a smaller number of larger reserves.

Gonad development and evidence of protogyny in the red‐throat emperor on the Great Barrier Reef - K. Bean; B. D. Mapstone; C. R. Davies; C. D. Murchie; A. J. Williams (Journal of Fish Biology, 2003)
The gonad development in the red‐throat emperor Lethrinus miniatus is described and the first detailed evidence for protogyny in this species provided. The identification of transitional individuals, bimodal sex‐specific size‐frequency distributions and female biased sex ratios suggest that L. miniatus is most likely a protogynous hermaphrodite. Transitional L. miniatus gonads were characterized by the concurrent degeneration of all oocytes and the proliferation of spermatocysts near the edge of the lamellae, an increase in blood vessels along strands of stromal tissue within the lamellae and the formation of multiple sperm sinuses. The sites of oocyte degeneration and proliferation of spermatocysts were spatially segregated. An increase in blood vessels along strands of stromal tissue within the lamellae of transitional phase gonads is likely to assist in the breakdown of oocytes and the proliferation of spermatocysts. Most mature resting females containing spermatocysts occurred within the transitional size‐frequency distribution, suggesting that the presence of spermatocysts in these females may be an early sign of sex change. Oocytes within female gonads were interrupted by filamentous strands of stromal tissue within the lamellae. The testis contained a remanent ovarian lumen but no residual oocytes. Three characteristics of transitional L. miniatus gonads were found to be unusual and described for few other species of coral reef fishes. These included the absence of oocytes within testes, increased numbers of blood vessels, and the presence of strands of stromal tissue within the lamellae.